Intervention program: integral diet and physical exercise in the reduction of anthropometric parameters in Salvador de Bahia-Brasil: Programa de intervención: dieta integral y ejercicio físico en la reducción de parámetros antropométricos en salvador de Bahia-Brasil - Cari Huanca, Gloria (2021)
Introduction: High rates in anthropometric parameters such as excess weight, body fat, visceral fat, hypertension generate serious problems that affect the health of the general population. Objective: To identify the effects produced by the intervention program "integral diet and physical exercise" on anthropometric parameters and blood pressure in a community in Salvador de Bahia. Methodology: Experimental intervention study lasting 40 days in which 31 adults participated, carried out in a neighborhood of the municipality of Salvador (Bahia), Brazil. The study consisted of administering a comprehensive diet based on whole grains, oilseeds, legumes, fruits, vegetables and total abstinence from foods of animal origin, refined, industrialized flours, sugar, following the "Healthy Plate" and Physical Exercise model. Results: The participants who followed the program of integral diet and physical exercise, obtained significant changes in the anthropometric values (weight, BMI, waist contour, percentage of body fat, abdominal fat, biological age, and systolic and diastolic blood pressure, (p <0.01), body mass did not show significant changes (p <0.57). Conclusion: The intervention program with a comprehensive plant-based diet and physical exercise can reduce the rates of obesity, abdominal fat, anthropometric perimeters and blood pressure and contribute to reducing potential problems of chronic non-communicable diseases.